Immature platelet indices alongside procalcitonin for sensitive and specific identification of bacteremia in the intensive care unit. (3rd October 2021) - Jones, Nathan; Tridente, Ascanio; Dempsey-Hibbert, Nina C.
Abstract: Hematological markers that can be rapidly analyzed and regularly monitored during a patient's stay on ICU, and that can identify bacterial causes of sepsis are being extensively sought. The significance of platelets in early immunological responses provides justification for assessing their usefulness in the identification of bacteremia amongst sepsis patients. In this preliminary study, the full blood count, including the platelet count by impedance (PLT-I), Immature Platelet Fraction (IPF%) and absolute immature platelet count (AIPC), were analyzed in eighty-two sepsis patients daily over the first 5 days stay on ICU. C-Reactive Protein (CRP), procalcitonin (PCT), and lactate were also analyzed daily. Blood cultures confirmed or excluded the presence of bacteremia. PCT provided the earliest indicator of bacteremia, with significant differences between the two cohorts on day 1. The change in IPF% and AIPC from day 1 to day 2 (Δ IPF% and Δ AIPC) provided the most accurate indication; A combination of Δ IPF% and day 2 PCT, provided a positive predictive value and negative predictive value of 100% and 96.10%, respectively. These data provide strong justification for larger multi-center validation studies to confirm the usefulness of these platelet indices during the assessment of sepsis on the ICU.